The Politics of Exclusion, or, Reanimating the Archive - van Alphen, Ernst (The Nordic Journal of Aesthetics, 2016)
The notion of the archive covers two kinds of knowledge: knowledge and memories that can be articulated and objectified by convergent discursive rules, and knowledge that remains overlooked because of the same discursive rules, now working as rules of exclusion. Many contemporary art practices foreground these exclusions from the archive by presenting them as yet another archive. Artists highlight this residue of the archive by collecting images that were until then not considered to be archivable, that is, of any value or importance. In this article I will discuss work of Santu Mofokeng, Akram Zataari, Walid Raad, and Darius Jablonski as examples of such archival artistic practices.